Dam break studies using hydrologic and hydraulics model for Chereh Dam, Kuantan, Pahang, Malaysia - Winarta, Bambang; Juwono, P. T.; Mohamad Idris, Ali; Noram Irwan, Ramli (IOP Publishing Ltd., 2019)
This current study is evaluating the risks of Chereh Dam failure. A dam break study basically consists of rainfall analyses; hydrologic modeling; dam breaching analysis and inundation mapping of the resultant flood. Precipitation analyses and development of Intensity Duration Frequency (IDF) curve has been prepared and published in Urban Storm water Management Manual by the Department of Irrigation and Drainage of Malaysia. In here, hydrologic modeling was performed with the HEC-HMS (Hydrologic Modeling System). The results of hydrological analysis revealed that the observed and simulated flow hydrographs in the calibration and confirmation exercises were reasonably close. Furthermore, dam breaching analysis and inundation mapping was executed with the HEC-RAS (River Analysis System). Dam break analysis result will be used to arrange policy of the state or city government in order to minimize the hazards of Chereh Dam failure.